Hospitalization, death, and probable reinfection in Peruvian healthcare workers infected with SARS-CoV-2: a national retrospective cohort study - Willy Ramos; Nadia Guerrero; Edwin Omar Napanga-Saldaña; José Medina; Manuel Loayza; Jhony A. De La Cruz-Vargas; María Vargas; Luis Ordóñez; Yovanna Seclén-Ubillús; Carlos Álvarez-Antonio; Juan Arrasco (BMC, 2022)
Abstract Background Peru has some of the worst outcomes worldwide as a result of the SARS-CoV-2 pandemic; it is presumed that this has also affected healthcare workers. This study aimed to establish whether occupation and other non-occupational variables were risk factors for possible reinfection, hospitalization, and mortality from COVID-19 in cohorts of Peruvian healthcare workers infected with SARS-CoV-2. Methods Retrospective cohort study. Healthcare workers who presented SARS-CoV-2 infection between March 1, 2020, and August 6, 2021, were included. Occupational cohorts were reconstructed from the following sources of information: National Epidemiological Surveillance System, molecular tests (NETLAB), results of serology and antigen tests (SICOVID-19), National Registry of Health Personnel (INFORHUS), and National Information System of Deaths (SINADEF). The incidence of probable reinfection, hospitalization, and death from COVID-19 was obtained in the cohorts of technicians and health assistants, nursing staff, midwives, dentists, doctors, and other healthcare workers. We evaluated whether the occupation and other non-occupational variables were risk factors for probable reinfection, hospitalization, and death from COVID-19 using log-binomial and probit binomial models, obtaining the adjusted relative risk (RRAJ). Results 90,398 healthcare workers were included in the study. Most cases were seen in technicians and health assistants (38.6%), and nursing staff (25.6%). 8.1% required hospitalization, 1.7% died from COVID-19, and 1.8% had probable reinfection. A similar incidence of probable reinfection was found in the six cohorts (1.7-1.9%). Doctors had a higher incidence of hospitalization (13.2%) and death (2.6%); however, they were also those who presented greater susceptibility linked to non-occupational variables (age and comorbidities). The multivariate analysis found that doctors (RRAJ = 1.720; CI 95: 1.569-1.886) had a higher risk of hospitalization and that the occupation of technician and health assistant was the only one that constituted a risk factor for mortality from COVID-19 (RRAJ = 1.256; 95% CI: 1.043-1.512). Conclusions Peruvian technicians and health assistants would have a higher risk of death from COVID-19 than other healthcare workers, while doctors have a higher incidence of death probably linked to the high frequency of non-occupational risk factors. Doctors present a higher risk of hospitalization independent of comorbidities and age; likewise, all occupations show a similar risk of probable reinfection.